(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 1999)
Extensive tracts of Devonian and older sedimentary and igneous units occur within the axial region of the western Karakoram Block of northernmost Pakistan over a distance in excess of 200 km between the the headwaters of the Karambar valley in northwestern Gilgit Agency to southwestern Chitral. Conodont data indicate that the oldest sedimentary unit so far discriminated within this belt, the Yarkhun Formation, includes horizons of Ordovician (Arenig) age, consistent with an earlier-presented acritarch-based Arenig age for part of the same unit. Conodont data from the "Lun Shales", a stratigraphic potpourri with little-known Silurian and Devonian tracts, demonstrate the presence of Early Devonian (early Emsian) horizons. The Shogrâm Formation, widely distributed through the region, spans an appreciable interval of the Middle and Late Devonian mid-Givetian through until at least early Famennian. A major lacuna in sedimentation may be present, represented by all or most of the earlier half of Frasnian time. A biostratigraphically and possibly biogeographically important new species, Icriodus homeomorphus, is described; it is encountered in horizons of early Famennian age (Late triangularis Zone to ?Early crepida Zone).